Kuwait Finance House - Dalal AlNoumani; Fawaz AlMutairi; Julian Machado (AIBPM Publisher, 2019)
This analysis will explore the corporate governance of the Kuwait Finance House. Given that the institution is a market leader, it encompasses the revolutionary financial mall concept whereby it groups together partners such as telecommunication, insurance and also credit card providers. The concept of the financial mall is providing a degree of ease through convenient services for customers, automated systems and also financial advisors. The analysis will explore the major challenge that Kuwait Finance House is facing and also the conflict of interest between the managers and the shareholders. The analysis will utilize descriptive research study whereby interviews will be conducted to get a scope of the operation of the institution. The analysis will offer recommendations such as involvement of the customers before internal growth investment. It should also establish the reason for the conflict between the shareholders and the managers and also why the financial house requires corporate governance. Given the bank has a separate clause that defines their creation of wealth for the shareholder, the conflict between the manager will eventually result in a stunted growth of the customer deposit, shareholder equity and the total assets which are important financial indicators.